Beyond Justice: Pufendorf and Locke on the Desire for Esteem. (October 2019) - Haara, Heikki; Stuart-Buttle, Tim
It is widely accepted that the seventeenth-century natural lawyers constructed the minimal requirement for social coordination between self-seeking individuals animated by the desire for self-preservation. On most interpretations, Grotius and his successors focused on the "perfect" duties (rules of justice) and had little to say about the "imperfect" duties of love and civility. This essay provides an alternative reading of post-Grotian natural law by reconstructing Pufendorf's and Locke's understanding of how the duties of civility and love might be realised in civil society. The essay argues that, for Pufendorf and Locke, the desire for esteem offers an explanation of how people recognize the content of the reciprocal duties of social morality and motivate themselves to act accordingly. The reconstruction of their views on the beneficial effects of esteem-seeking points towards a new interpretation of how, and why, philosophical interest in an economy of esteem and the social nature of the self emerged, prior to their treatment by eighteenth-century authors such as Hume and Smith.